ANALYSIS OF RELATIONSHIPS OF CELL IMMUNITY INDICATORS OF COWS AFTER POSTNATAL ENDOMETRITIS - Bodnar, A.O. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
In recent years, it has been proven that immune phenomena in the body of females change dynamically at all stages of both physiological and pathological state of the reproductive system. Immune disorders accompany the development of various pathologies in the genitals of cows - inflammatory, dystrophic, degenerative in nature. It is well known that products produced in the reproductive organs actively affect the immune status of mammals. Thus, during pregnancy and the early postpartum period, both the quantitative and qualitative composition of immunocompetent cells in the peripheral blood of females changes. Immune disorders accompany the development of various pathologies in the genitals of females, both inflammatory and dystrophic in nature. The content of immunocompetent cells in the peripheral blood was determined in the reactions of: T-lymphocytes - spontaneous rosette formation of cells (E-RFC) with sheep erythrocytes, B-cells - by the method of complementary E-RFC. Determination of the content of subpopulations of T-lymphocytes (Tm-helpers and Tg-suppressors) was performed in the reactions of RFC using sera against immunoglobulins in cattle. Assessment of the functional state of the immune system of patients was additionally performed by determining and analyzing the integrated indicators: T-index, the ratio of T: B and Tm: Tg cells. It was found that there is a direct correlation between the absolute values of B-, T-, Tμ-, Tγ- and O-lymphocytes in the blood, which indicates a certain affinity of these mononuclear populations. Here we should distinguish the average relationship between T- and B-lymphocytes (r = 0.68) and T- and O-lymphocytes (r = 0.48). This picture can be explained by the complex and negative impact on the mechanisms of immune defense and hematopoiesis of inflammatory mediators and toxins coming from the uterus, as well as the dynamic hormonal adjustment of the female body after childbirth. Thus, at the end of treatment and clinical recovery of females, there was a sharp (almost double) decrease in the strength of the direct relationship between the level of B-lymphocytes and T-index and an increase of 4 times the negative correlation between B-cells and T: B - coefficient indicates a certain normalization of T- and B-links of immunity. Also logical are the dynamic changes in the T-level of the immune defense of cows, which have recovered clinically: doubled the positive correlation between the content of T-cells in the blood and their subpopulations, almost 3 times increased the direct relationship between T-lymphocytes and T: B -relationship, as well as a sharp change in the correlation coefficient (with a change from positive to negative) between T- and O-lymphocytes. Correlation analysis of cellular immunity indicates the presence of stable relationships between the content in the venous blood of cows T-lymphocytes and their main subpopulations and immunoregulatory coefficients. Restoration of the clinical status of cows with purulent-inflammatory pathology of puerperium is accompanied by normalization of immunological parameters of their body and positive changes in the relationship between absolute and relative indicators of immunocompetent cells, which can be used to predict the postpartum period, diagnose inflammatory processes and monitoring the effectiveness of treatment